Beyond the Badge: The Determinants of Indonesian Public-Servant Performance - Ahmad, Ahmad; Azis, St. Nurhayati; Murfat, Moh Zulkifli (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
Indonesia's public servants struggle to match the comparative performance of its top ASEAN peers, potentially due to an underdeveloped workforce. This study, drawing on insights from 214 public servants, delves deeper to identify key performance drivers. Surprisingly, this analysis, using a Structural Equation Model, reveals no significant link between organizational culture and employee commitment, motivation, or performance. Instead, the study pinpoints competency mismatch as the critical factor hindering effectiveness. Actionable insights emerge, highlighting the need for strategic skill development programs tailored to individual roles and responsibilities. Furthermore, the research underscores the current emphasis on behavioral factors, calling for a shift towards targeted interventions that modify employee behavior and drive performance improvement.